Consumer protection in blockchain-based metaverses: a comparative study of cross-border legal gaps and platform governance - López Rodríguez, Ana Mercedes (Frontiers in Blockchain, 2025)
Blockchain-based metaverse platforms such as Decentraland and The Sandbox offer a vision of decentralized digital ownership and seamless cross-border interaction, yet expose users to significant legal and security risks due to fragmented consumer protection frameworks. This article undertakes a comparative legal analysis of six major jurisdictions—the European Union, United States, China, Singapore, Brazil, and South Korea—focusing on jurisdictional issues, data privacy, liability, and dispute resolution within decentralized virtual worlds. The findings reveal a fragmented regulatory landscape, with ongoing gaps that contribute to declining user trust and engagement. These unresolved legal challenges, alongside persistent security vulnerabilities, undermine the long-term viability of metaverse ecosystems. To address these problems, the paper proposes a hybrid governance framework that integrates blockchain-native tools, such as smart contract arbitration, with enforceable legal standards. This approach aims to align innovation with accountability and foster a more trustworthy, sustainable, and user-centered metaverse.